2012
DOI: 10.1039/c1em10688k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, certification and interlaboratory analysis of workplace air filters spiked with high-fired beryllium oxide

Abstract: Occupational sampling and analysis for multiple elements is generally approached using various approved methods from authoritative government sources such as the National Institute for Occupational Safety and Health (NIOSH), the Occupational Safety and Health Administration (OSHA) and the Environmental Protection Agency (EPA), as well as consensus standards bodies such as ASTM International. The constituents of a sample can exist as unidentified compounds requiring sample preparation to be chosen appropriately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…17, 18 However, nitric acid is not as efficient as stronger acids (i.e., hydrofluoric acid) at yielding a higher proportion of the metals encapsulated in crystalline minerals. 42 These minerals, like feldspar and quartz contribute more to the larger particle size fractions. Some of the previous studies obtained total metal concentration via instrumental neutron activation analysis from outdoor dust samples and also observed that smaller size fractions have higher concentrations of metals.…”
Section: Discussionmentioning
confidence: 99%
“…17, 18 However, nitric acid is not as efficient as stronger acids (i.e., hydrofluoric acid) at yielding a higher proportion of the metals encapsulated in crystalline minerals. 42 These minerals, like feldspar and quartz contribute more to the larger particle size fractions. Some of the previous studies obtained total metal concentration via instrumental neutron activation analysis from outdoor dust samples and also observed that smaller size fractions have higher concentrations of metals.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, MCE filters are used for air sampling and Whatman filters have been used for surface sampling. Certified MCE filters 21 spiked with known quantities of aqueous beryllium standards (diluted from 1000 μg ml −1 standard solution) and National Institute of Standards and Technology Standard Reference Material (NIST SRM ® ) 1877 beryllium oxide (NIST, Gaithersburg, MD, USA) were provided by High-Purity Standards (North Charleston, SC, USA). Certified reference material (CRM) soils with established beryllium contents were obtained from NIST and from the Canadian Certified Reference Materials Project (CCRMP, Ottawa, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Our measurement of Be in SRM 2587 was high by about 50 %; this result may be due to uncertainty in the "information" Be concentration. A recent beryllium oxide powder standard (NIST SRM 1877) may be used in future analyses to determine recovery of beryllium oxide, particularly in matrix-matched samples (Winchester et al, 2009 andOatts et al, 2012). The high-fired beryllium oxide standard is more representative of the process-induced contamination that is likely to be found in beryllium handling and machining facilities.…”
Section: Recent Multi-element Analysis Of Selected Historical Soil Amentioning
confidence: 99%